If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12t + -18 = 4(4t + 2) Reorder the terms: -18 + 12t = 4(4t + 2) Reorder the terms: -18 + 12t = 4(2 + 4t) -18 + 12t = (2 * 4 + 4t * 4) -18 + 12t = (8 + 16t) Solving -18 + 12t = 8 + 16t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-16t' to each side of the equation. -18 + 12t + -16t = 8 + 16t + -16t Combine like terms: 12t + -16t = -4t -18 + -4t = 8 + 16t + -16t Combine like terms: 16t + -16t = 0 -18 + -4t = 8 + 0 -18 + -4t = 8 Add '18' to each side of the equation. -18 + 18 + -4t = 8 + 18 Combine like terms: -18 + 18 = 0 0 + -4t = 8 + 18 -4t = 8 + 18 Combine like terms: 8 + 18 = 26 -4t = 26 Divide each side by '-4'. t = -6.5 Simplifying t = -6.5
| 5-3=22 | | 2[k-(2k+8)+6]=2(k+2) | | 5n=2+2+2+2+2 | | 7-9=48 | | 4-8=60 | | 4x+12y=780 | | 350-280=70 | | 2(4x+5)-3=0 | | 6X-X^2-9=0 | | 2+7=45 | | 4(5x+10)=10(2x+4) | | 4x^2-10=-13x-7x | | 2n(3n-3)=0 | | 6y+1x=372 | | 7-3=48 | | y^3+x^2+3=123 | | 6=y-2x | | 3+7=40 | | 5x+5(x-6)=5(x-5) | | 6+3=36 | | 8x+8y=240 | | .33333x-21=33 | | 3x+12=2x+6 | | t*2+4t*2= | | 3h+28=82 | | 6+3=56 | | 4(2x)+4(3x)= | | 14+5x=(-x+3)-11 | | -13x+16=10 | | 2x-25+3x+x+6+4x-11=360 | | -4x-2(8x+1)=-2x-10 | | 4+3=56 |